Provision of clinical pharmacy services during the COVID-19 pandemic: Experiences of pharmacists from 16 European countries - OKUYAN, BETÜL (ELSEVIER SCIENCE INC, 2021)
Background: The pharmacy profession has an important role in the frontline healthcare response to COVID-19 across all settings. Objective: This study sought to explore the views and experiences of clinical pharmacists in relation to the provision of clinical pharmacy services during COVID-19. Methods: Semi-structured qualitative interviews were conducted with pharmacists working in clinical roles in healthcare settings across Europe. Participants were recruited through professional organisations of clinical and hospitals pharmacists combined with a snowballing technique. The Pharmacy Emergency Preparedness and Response Framework and Disaster Preparedness Framework for pharmacy services were used to generate data which were analysed using the thematic framework method. Results: Twenty-two participants from 16 European countries described a range of measures to protect patients, public and healthcare staff against virus transmission including developing and disseminating educational materials. Most described their involvement in aspects of evidence provision such as facilitating clinical trials, gathering and appraising evidence and disseminating clinical information. Many hospital-based pharmacists were reassigned to new roles such as intensive care. Routine clinical services were extensively interrupted and remote forms of communication were used. Most were motivated by a strong sense of professionalism to continue delivering services. A number of facilitators and barriers to prevention, preparedness and response actions were identified which related to uptake of new roles, recognition of pharmacists roles in the healthcare team, information gathering, communication with patients and healthcare professionals, and provision of routine clinical services. Conclusions: Participants in this multinational qualitative study described a range of service adaptations and adoption of novel roles to prevent and mitigate the public health impact of the pandemic. The study findings may help to inform governments, public health agencies and healthcare systems in harnessing ongoing service provision and adapt to any future interruptions.
Keywords: COVID-19; Coronavirus; Pandemic; Pharmacist; Clinical pharmacy; Pharmaceutical care; QUALITATIVE RESEARCH; ENGLAND; IMPACT; CARE